Fast Aberrations Compensation in Digital Holographic Microscopy Based on Phase Transformation - Dingnan Deng; Weijuan Qu (IEEE Photonics Journal, 2020)
A fast aberrations compensation method for digital holographic microscopy based on phase transformation is proposed. Phase transformation for original unwrapped phase can be done using rotation transformation with 180° and reflection transformation. Not only off-axis tilt but also phase curvature is compensated with simple algebraic operation between original unwrapped phase and transformation phase. The proposed scheme is fast and automatic but avoids the requirements of fitting operation and prior parameters of specimen/system. Simulation and experiment results demonstrate the availability of proposed method.